2016
DOI: 10.1021/acs.energyfuels.5b02984
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alkali and Alkaline Earth Metals on in-Situ Catalytic Fast Pyrolysis of Lignocellulosic Biomass: A Microreactor Study

Abstract: In-situ catalytic fast pyrolysis (CFP) is considered to be a promising pathway to produce aromatic hydrocarbons from lignocellulosic biomass. However, the presence of variable amounts of inorganic ash in biomass in the form of alkali and alkaline earth metals (AAEMs) is a concern while using in situ catalysts because AAEMs could influence product distribution from CFP while also being a major reason for catalyst deactivation. In this study, the effect of four alkali and alkaline earth metals (K, Na, Mg, and Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(85 citation statements)
references
References 35 publications
6
76
2
1
Order By: Relevance
“…Increased relative yields of CO 2 and methanol in 2PN are indicated by negative PC1 loadings, which can be attributed to the higher ash and inorganics content in 2PN. Ash and particularly AAEMs are more reactive than other inorganics and effectively catalyze ring-breaking, depolymerization, and fragmentation reaction, which results in increased production of non-condensable gases, organic acids, and other light oxygenated compounds (Carpenter et al, 2014;Mahadevan et al, 2016b). Similar trends are observed in the PCA results obtained from the Py-GC/MS data for SG, 6PN, and their blends ( Figure S1).…”
Section: Py-gc/ms Of Blended Samplessupporting
confidence: 72%
See 3 more Smart Citations
“…Increased relative yields of CO 2 and methanol in 2PN are indicated by negative PC1 loadings, which can be attributed to the higher ash and inorganics content in 2PN. Ash and particularly AAEMs are more reactive than other inorganics and effectively catalyze ring-breaking, depolymerization, and fragmentation reaction, which results in increased production of non-condensable gases, organic acids, and other light oxygenated compounds (Carpenter et al, 2014;Mahadevan et al, 2016b). Similar trends are observed in the PCA results obtained from the Py-GC/MS data for SG, 6PN, and their blends ( Figure S1).…”
Section: Py-gc/ms Of Blended Samplessupporting
confidence: 72%
“…In addition, previous work demonstrates that the presence of ash, especially AAEMs, results in greater formation of organic acids, non-condensable gases, and char during pyrolysis (Fahmi et al, 2008;Patwardhan et al, 2010;Mahadevan et al, 2016b).…”
Section: Feedstock Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the investigations performed by Mahadevan et al [44] indicated that contamination of the catalyst surface by alkali or alkaline earth metals (especially Na, K, or Ca) present in biomass feedstock resulted in a reduction in the amount of aromatic hydrocarbons and olefins, with a simultaneous increase in the yield of permanent gases and char. The presented literature data demonstrate that an introduction of metals on the surface of zeolites or mesoporous silicas (i.e., by impregnation or ion-exchange methods) leads to an increase in the value of the bio-oil produced.…”
Section: Modification Of Zeolites and Mesoporous Materials By The Addmentioning
confidence: 99%